1998
DOI: 10.1111/j.1745-4530.1998.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

OHMIC HEATING OF SOLID‐LIQUID MIXTURES: A COMPARISON OF MATHEMATICAL MODELS UNDER WORST‐CASE HEATING CONDITIONS1

Abstract: A critical issue in the modeling of ohmic heating of solid-liquid mixtures is the understanding of worst-case scenarios, and in particular, the reliability of mathematical models under such conditions. This study involves examination of two alternative published formulations, one involving the use of circuit theory and a well-mixed fluid assumption, against another formulation, involving the solution to Laplace's equation, but without convective effects. As apected, the models (and an analytical solution) yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 7 publications
1
40
0
Order By: Relevance
“…4). Sastry and Salengke (1998) used a Circuit Analogy, Mixed Fluid (CAMF) model for a simulation study on the ohmic heating of solid-liquid mixtures. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Sastry and Salengke (1998) used a Circuit Analogy, Mixed Fluid (CAMF) model for a simulation study on the ohmic heating of solid-liquid mixtures. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sastry and Palaniappan (1992) developed a three-dimensional finite element model for the ohmic heating of particle-liquid mixtures and found that the EC and volume fraction of each phase were the critical parameters affecting the heating rate. Sastry and Salengke (1998) compared two mathematical models (the Circuit Analogy, Mixed Fluid model and the Laplace Equation, No-convection model) for the ohmic heating of solid-liquid mixtures (with single particle only) under worst-case heating scenarios (solid and liquid with very different EC). Using finite element software, Fu and Hsieh (1999) performed a simulation of a two-dimensional static ohmic heating system containing one single rectangular particle.…”
Section: Introductionmentioning
confidence: 99%
“…12 and 13 different voltage gradients were applied for apricot and peach purees, respectively. Electrical conductivities of samples were calculated from voltage and current data using the following equation (Sastry & Salengke, 1998;Wang & Sastry, 1993):…”
Section: Methodsmentioning
confidence: 99%
“…Although conventional thermal pasteurisation still represents the most available and best understood technique, it may affect functional properties of egg products: the coagulation, the foaming and the emulsifying properties and the degradation of quality (Góngora-Nieto et al 2003;Hermawan et al 2004;Nolsoe and Undeland 2009). Ohmic heating is an alternative heating system for pumpable foods which is based on the passage of electrical current through a food product which serves as an electrical resistance (Reznick 1996;Sastry and Salengke 1998;Icier 2003). Ohmic heating yields better products, clearly superior in quality than those processed by conventional heating (Allali et al 2008).…”
Section: Introductionmentioning
confidence: 99%